Immunologic aspects of migraine: A review of literature - Salahi, Mehrnaz; Parsa, Sina; Nourmohammadi, Delaram; Razmkhah, Zahra; Salimi, Omid; Rahmani, Mohammadreza; Zivary, Saeid; Askarzadeh, Monireh; Tapak, Mohammad Amin; Vaezi, Ali; Sadeghsalehi, Hamidreza; Yaghoobpoor, Shirin; et al. (Frontiers in Neurology, 2022)
Migraine headaches are highly prevalent, affecting 15% of the population. However, despite many studies to determine this disease's mechanism and efficient management, its pathophysiology has not been fully elucidated. There are suggested hypotheses about the possible mediating role of mast cells, immunoglobulin E, histamine, and cytokines in this disease. A higher incidence of this disease in allergic and asthma patients, reported by several studies, indicates the possible role of brain mast cells located around the brain vessels in this disease. The mast cells are more specifically within the dura and can affect the trigeminal nerve and cervical or sphenopalatine ganglion, triggering the secretion of substances that cause migraine. Neuropeptides such as calcitonin gene-related peptide (CGRP), neurokinin-A, neurotensin (NT), pituitary adenylate-cyclase-activating peptide (PACAP), and substance P (SP) trigger mast cells, and in response, they secrete pro-inflammatory and vasodilatory molecules such as interleukin-6 (IL-6) and vascular endothelial growth factor (VEGF) as a selective result of corticotropin-releasing hormone (CRH) secretion. This stress hormone contributes to migraine or intensifies it. Blocking these pathways using immunologic agents such as CGRP antibody, anti-CGRP receptor antibody, and interleukin-1 beta (IL-1β)/interleukin 1 receptor type 1 (IL-1R1) axis-related agents may be promising as potential prophylactic migraine treatments. This review is going to summarize the immunological aspects of migraine.